Another Milestone for the Future of Education – A Summary of a Half-Century - Arató, Ferenc (Autonomy and Responsibility Journal of Educational Sciences, 2023)
Another Milestone for the Future of Education – A Summary of a Half-Century Davidson, N. (Ed.) (2021). Pioneering Perspectives in Cooperative Learning - Theory, Research, and Classroom Practice for Diverse Approach to CL. Routledge.